2021
DOI: 10.1097/tp.0000000000003834
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soluble Mediators of Innate Immune System Activation in Solid Allograft Rejection

Abstract: During the past years, solid allograft rejection has been considered the consequence of either cellular-or antibody-mediated reaction both being part of the adaptive immune response, whereas the role of innate immunity has been mostly considered less relevant. Recently, a large body of evidence suggested that the innate immune response and its soluble mediators may play a more important role during solid allograft rejection than originally thought. This review will highlight the role of novel soluble mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
2
3
0
2
Order By: Relevance
“…All our results collectively point to monocytes, which have recently emerged at the forefront of research in transplantation, 28-31 as main miRNA source. This major finding is thus extensively discussed in Supplemental Discussion ( SDC , http://links.lww.com/TP/C605).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…All our results collectively point to monocytes, which have recently emerged at the forefront of research in transplantation, 28-31 as main miRNA source. This major finding is thus extensively discussed in Supplemental Discussion ( SDC , http://links.lww.com/TP/C605).…”
Section: Discussionsupporting
confidence: 61%
“…25 Moreover, RORA may regulate the activity of signaling receptors and transmembrane transporters in human monocytic THP-1 cell line and endothelial cell lines. 26,27 All our results collectively point to monocytes, which have recently emerged at the forefront of research in transplantation, [28][29][30][31] as main miRNA source. This major finding is thus extensively discussed in Supplemental Discussion (SDC, http://links.lww.com/TP/C605).…”
Section: Discussionsupporting
confidence: 59%
“… 25 Notably, the KEGG pathway of DEGs was enriched in allograft rejection, which is a part of the adaptive immune response. 26 Previous studies have also revealed a key role for immune cells in the initiation, metastasis, and recurrence of HCC. 27 , 28 Therefore, it is necessary to reveal the potential mechanism of HCC relapse and identify potential predictive targets, with emphasis on immune repertoire profiling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent studies suggest that innate immune cells may be targeted in vivo to promote transplant tolerance by stimulating or inhibiting various signaling pathways, including microRNA (miRNA) and purinergic signaling ( 262 265 ). Usuelli et al found that suppression of miRNA-21 prevented allograft rejection and chronic allograft vasculopathy in a murine model of cardiac transplantation by promoting M2 polarization in infiltrating macrophages ( 262 ).…”
Section: Discussionmentioning
confidence: 99%